Association Between Early Antibiotic Therapy and In-Hospital Mortality Among Older Patients With SARS-CoV-2 Pneumonia. Issue 4 (17th July 2021) - Putot, Alain; Bouiller, Kevin; Laborde, Caroline; Gilis, Marine; Fèvre, Amélie; Hacquin, Arthur; Manckoundia, Patrick; Hoefler, Florence; Bermejo, Messaline; Mendes, Aline; Serratrice, Christine; Prendki, Virginie; et al.
Abstract: Background: It is uncertain whether antibiotic therapy should be started in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pneumonia. We aimed to investigate the association between early antibiotic therapy and the risk of in-hospital mortality in older patients. Methods: We performed a retrospective international cohort study (ANTIBIOVID) in 5 coronavirus disease 2019 geriatric units in France and Switzerland. Among 1357 consecutive patients aged 75 or older hospitalized and testing positive for SARS-CoV-2, 1072 had radiologically confirmed pneumonia, of which 914 patients were still alive and hospitalized at 48 hours. To adjust for confounders, a propensity score for treatment was created, and stabilized inverse probability of treatment weighting (SIPTW) was applied. To assess the association between early antibiotic therapy and in-hospital 30-day mortality, SIPTW-adjusted Kaplan–Meier and Cox proportional hazards regression analyses were performed. Results: Of the 914 patients with SARS-CoV-2 pneumonia, median age of 86, 428 (46.8%) received antibiotics in the first 48 hours after diagnosis. Among these patients, 147 (34.3%) died in hospital within 1 month versus 118 patients (24.3%) with no early antibiotic treatment. After SIPTW, early antibiotic treatment was not significantly associated with mortality (adjusted hazard ratio, 1.23; 95% confidence interval, 0.92–1.63; p = .160). Microbiologically confirmed superinfections occurred rarely in both groups (bacterial pneumonia: 2.5% vs 1.5%, p = .220; blood stream infection: 8.2% vs 5.2%, p = .120; Clostridioides difficile colitis: 2.4% vs 1.0%, p = .222). Conclusions: In a large multicenter cohort of older inpatients with SARS-CoV-2 pneumonia, early antibiotic treatment did not appear to be associated with an improved prognosis.